Evaluation of desensitizing efficacy of nanohydroxyapatite on the treatment of dentine hypersensitivity following ultrasonic scaling: a randomized controlled trial - Alsen, Walla; Barngkgei, Imad; Dayoub, Solayman (Brazilian Dental Science, 2022)
Objective: This randomized controlled trial aimed to compare nanohydroxyapatite with fluoride on managing post ultrasonic scaling Dentine hypersensitivity (DH). Material and Methods: Thirty patients (aged 20-50 years) with post ultrasonic-scaling DH were included in this study. The sample was randomly divided into three equal groups of 60 teeth each: the first group received nanohydroxyapatite material, the second group received fluoride material and the third group received sterile water as a placebo (controls). The materials were applied once for each patient. All patients were instructed to rate the level of pain before treatment, and after 1 hour, 24 hours, 2 weeks and 1 month on the numerical rating scale (NRS). The Kruskal-Wallis test, Mann-Whitney tests, linear regression analysis were used for the statistical analysis. Significance level was set at 0.05. Results: Both nanohydroxyapatite and fluoride were successful in reducing pain associated with DH when compared with the placebo in subsequent follow-ups (p < 0.05). However, one-hour and one-day post application, nanohydroxyapatite could reduce hypersensitivity pain more effectively than fluoride (p < 0.05). Conclusion: Nanohydroxyapatite material was found to be significantly more effective in reducing the DH that followed ultrasonic scaling one-hour and one-day post application as compared to fluoride and sterile water. Both fluoride and nanohydroxyapatite had similar effect on DH after two-weeks and one-month after application. KEYWORDS Dentine hypersensitivity; Desensitizing agent; Fluoride; Nanohydroxyapatite; Ultrasonic scaling.